2013
DOI: 10.1097/sih.0b013e3182689aff
|View full text |Cite
|
Sign up to set email alerts
|

To Die or Not To Die? A Review of Simulated Death

Abstract: Simulation as an educational technique is increasingly used in health care to teach about managing critical events and life-threatening situations and, infrequently, to teach about death. There is considerable controversy over whether to allow the simulator to die during a session when death is not a predefined learning objective. Some educators never allow the simulator to die unless death is the objective of the scenario, and others allow the simulator to die unexpectedly during any scenario. We do not know … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
67
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(70 citation statements)
references
References 19 publications
0
67
0
3
Order By: Relevance
“…Even in a comprehensive and user-friendly mock code manual, death is not covered in a practical fashion: it is listed only as an anticipated complication. 4 Our third finding is that our participants did not agree with many experts in simulation who recommend that if death is a possibility, trainees should be informed of this before each mock code 7,10 ; this is supposed to ensure that trainees perform in a nonthreatening environment. A study in medical students has indeed shown that participants exposed to a simulated patient death reported increased cognitive load.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Even in a comprehensive and user-friendly mock code manual, death is not covered in a practical fashion: it is listed only as an anticipated complication. 4 Our third finding is that our participants did not agree with many experts in simulation who recommend that if death is a possibility, trainees should be informed of this before each mock code 7,10 ; this is supposed to ensure that trainees perform in a nonthreatening environment. A study in medical students has indeed shown that participants exposed to a simulated patient death reported increased cognitive load.…”
Section: Discussionmentioning
confidence: 91%
“…6 There is considerable controversy over whether to allow the manikin to die during mock codes. 7,8 This academic debate consists mainly of expert opinion, lacking empirical information about trainees' opinions and experience. The goal of this study was to evaluate trainees' perspectives regarding neonatal mock codes and to examine the effects of the simulated death of the manikin.…”
Section: What This Study Addsmentioning
confidence: 99%
“…Na área médica, cenários que envolvem a morte são recomendados para aprendizes mais avançados, tais como residentes, staff e enfermeiras de grau avançado, enquanto para estudantes de medicina somente em circunstâncias especiais. Nesses casos recomenda-se que haja um pre-briefing, ou seja, uma sessão prévia à simulação, em que se coloca a possibilidade de morte na simulação que se seguirá [5,6]. O debriefing é o processo pós simulação, que envolve a participação ativa dos aprendizes guiados por um instrutor, também chamado de facilitador, que coordena a análise da simulação recém desenvolvida.…”
Section: Introductionunclassified
“…1Y5 The use of mannequin death is one such area. 4,6 One influential taxonomy divides mannequin death into the following 3 categories: ''expected death,'' where both facilitators and learners are aware that death is part of the subject matter; ''unexpected death,'' where mannequin death is planned by facilitators but learners are not alerted; and ''death due to action or inaction,'' where mannequin death is both unplanned by facilitators and unexpected by learners. 7 In this last category, mannequin death is dynamically introduced into a case because of perceived learner error or inappropriate decision making.…”
mentioning
confidence: 99%